Growth and Characterization of CZTS Thin Films Synthetized by Electrodeposition Method for Photovoltaic Applications. Issue 1 (November 2020) - Ziti, Ahmed; Hartiti, Bouchaib; Labrim, Hicham; Fadili, Salah; Batan, Abdelkrim; Ridah, Abderraouf; Thevenin, Philippe
Abstract: In the present work we deposited CZTS absorber material using a one-step electrodeposition method on ITO glass substrates. We studied the effect of sulfurization temperature on structural, morphological and optical properties of CZTS thin films sulfurized in N2 +H2 S atmosphere at 350, 375, 400 and 425°C for 10 min respectively for 10 min. The films have been charaterized by different techniques including X-ray diffractometer (XRD), Raman spectroscopy, scanning electron microscopy (SEM) and UV-visible-NIR spectrophotometer. XRD patterns indicated kesterite CZTS with preferential orientation along (112) plane, the intensity of peaks increased with increase of sulfurization temperature signified the amelioration of the crystallinity with sulfurization temperature increased, the estimated crystallite size are in the range of 14.27-37.32 nm. Raman scattering experiments confirmed the presence of CZTS thin films by the characteristic peak at 336 cm −1 . SEM images showed the morphology of CZTS thin films improved with increasing of sulfurization temperature. UV-Visible-NIR spectrophotometer showed that the values of optical absorption coefficient are larger than 10 4 cm −1 and optical band gap energy of CZTS thin films decreased with increasing of sulfurization temperature ranging 1.56 and 1.66 eV. These results make the electrodeposited CZTS films a suitable material as absorber material in solar cells applications based thin films.